Function of Polymers in Encapsulation Process - Aboudzadeh, M. Ali; Hamzehlou, Shaghayegh (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
An interdisciplinary book that brings together, at an international level, a high-quality collection of reviews and original research articles dealing with the importance of natural or synthetic polymers in encapsulation processes and their applications. A deep understanding and relevant theoretical calculations for exploring the functions of the materials (involved in the formulations) have also been presented along with fundamental investigations. This book has explored the latest research on the function of polymers in encapsulation technology including fundamental theory and experiments together with reviews and articles. Moreover, the present book offers easy-to-achieve approaches that have been developed so far and could create a platform for industrial material production.